The Strategy of Geography Teachers in Implementing Standards Process of Permendikbud Number 22 the Year 2016 on Geography Learning in SMA Negeri Solok Regency - Helmi, Dewilna; Febriandi, Febriandi (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research to know the implementation of standard process that consists of analyzing the lesson plan that prepared by the teacher, analyzing the implementation of learning process, seeing the constraints in implementing the standard process, formulating the teacher strategy in implementing process standard and decreasing the priority of policy direction in implementing process standard in SMA Negeri Solok Regency. The type of research used a mixed method which combines qualitative and quantitative research. Data were collected through, observation, interview, and documentation. Data analysis methods consist of reduction, presentation and verification, SWOT analysis and Interpretive Structural Modeling. The results of the research indicate that: 1) the implementation of standards process seen in the teacher's learning plan has designed syllabus and lesson plan but not fully in accordance with the steps and components of RPP preparation.2) In the implementation of classroom management learning process still not fully in accordance with standards process. Judging from the methods, models, media mastery of the material has not been effective and efficient according to the 2013 curriculum this was due to the lack of understanding of teachers towards the curriculum of 2013, from the assessment of learning outcomes in all three aspects of the assessment conducted only the assessment of knowledge, to attitudes assessment and skills not implemented maximally. 3) The obstacle faced is the unavailability of time in the preparation of the implementation plan of learning because the burden of teaching is high enough, difficulties in the implementation of learning are influenced by low student learning interest and in the assessment of learning still constrained by time. 4) There were nine strategies derived from field research. 5) Priority policy directives that arise to improve the implementation of process standards in geography learning were: Increased interest of teachers in training activities held in MGMP forums so as to improve teacher competence, Curriculum Training 2013 to improve understanding of the reforms conducted in ministerial regulations, academic supervision by school principals and teachers to improve teachers' ability to manage the classroom, and to develop media and interesting learning resources to foster student interest in learning.